Implementación de un servidor de telefonía ip con linux elastix en el laboratorio de redes de la carrera de ingeniería en informática y sistemas computacionales de la Universidad Técnica de Cotopaxi, ubicado en la ciudad de Latacunga, provincia de Cotopaxi, en el período de junio 2014 - febrero 2015 - Chugchilan Ronquillo, Cristian Paúl (2015)
This research project detailing the implementation of an IP telephony server, same as was configured laboratory networks Career in Computer Engineering and Computer Systems at the Technical University of Cotopaxi, the IP telephony server improves the performance, communication and transmission of information whether you messages, text, video calls, among others. Linux Elastix is a free distribution of unified communications server that integrates into one package functions or services such as instant messaging, email, fax, VoIP PBX, among others, and was used Elastix allows for the implementation of IP telephony server all these services by implementing much of its functionality on Asterisk, Hylafax, Openfire and Postfix, this server also has an easy GUI to understand and use....